A Pilot Study on Blood Components in COVID-19 Affected Subjects: A Correlation to UPR Signalling and ER-Stress - Bansal, Akash; Kumar, Sushil; Rai, Neha; Kumari, Shilpi; Kumar, Visesh; Kumar, Ajeet; Chandra, Nimai Chand (Indian journal of clinical biochemistry, 2023)
The endoplasmic reticulum (ER) is the site for protein synthesis, its folding and secretion. An intricate set of signalling pathways, called UPR pathways, have been evolved by ER in mammalian cells, to allow the cell to respond the presence of misfolded proteins within the ER. Breaching of these signalling systems by disease oriented accumulation of unfolded proteins may develop cellular stress. The aim of this study is to explore whether COVID-19 infection is responsible for developing this kind of endoplasmic reticulum related stress (ER-stress). ER-stress was evaluated by checking the expression of ER-stress markers e.g. PERK (adapting) and TRAF2 (alarming). ER-stress was correlated to several blood parameters viz. IgG, pro- and anti-inflammatory cytokines, leukocytes, lymphocytes, RBC, haemoglobin and PaO 2 /FiO 2 ratio (ratio of arterial oxygen partial pressure to fractional inspired oxygen) in COVID-19 affected subjects. COVID-19 infection was found to be a state of protein homeostasis (proteostasis) collapse. Changes in IgG levels showed very poor immune response by the infected subjects. At the initial phase of the disease, pro-inflammatory cytokine levels were high and anti-inflammatory cytokines levels were low; though they were partly compromised at later phase of the disease. Total leukocyte concentration increased over the period of time; while percentage of lymphocytes were dropped. No significant changes were observed in cases of RBC counts and haemoglobin (Hb) levels. Both RBC and Hb were maintained at their normal range. In mildly stressed group, PaO 2 /FiO 2 ratio (oxygenation status) was in the higher side of normal range; whereas in other two groups the ratio was in respiratory distress syndrome mode. Virus could induce mild to severe ER-stress, which could be the cause of cellular death and systemic dysfunction introducing fatal consequences. Graphical Abstract Schematic representation of SARS-CoV-2 infection and related consequences.